Dynamics of weak interaction in a system of similar species - E. V. Gorchakova (Моделирование и анализ информационных систем, 2011)
The dynamics of the system what describes the interaction between two similar species is investigated. The normal form is constructed, it is reduced to a normal form of a system of diffused weakly connected Hutchinson equations.